LOCAL WISDOM: CAN IT MITIGATE THE RISK OF FRAUD? - Yosua Febrian Putra Aditya; Aprina Nugrahesthy Sulistya Hapsari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
The risk of fraud in managing village funds is increasingly proportional to the increasing amount of funds provided by the central government every year. One of the ways that the government can use to mitigate the risk of fraud is to implement local wisdom. This research was conducted to identify the fraud risk that occurs in managing village funds in Kebonan Village and analyze local wisdom as one of the media to mitigate fraud in the management of village funds in the village. This research uses descriptive qualitative data method with primary data sources. The instrument used in the study was a semi-structured interview. The result of this study shows that even though there is already control to reduce and manage every fraud risk, local wisdom also can be used as a means of mitigating the fraud risk if it is properly imbued.